Galectin‐3 Predicts Left Ventricular Remodeling of Hypertension. Issue 6 (22nd December 2015) - Yao, Yongwei; Shen, Dongli; Chen, Rong; Ying, Chunyang; Wang, Chenghua; Guo, Junfang; Zhang, Guohui
Abstract : Previous studies have suggested that galectin‐3 is an important mediator of cardiac fibrosis. The aim of this study was to investigate the utility of galectin‐3 in identifying early left ventricular remodeling (LVRM) in patients with hypertension. A total of 107 patients with hypertension and 108 controls were enrolled in this study. The levels of galectin‐3 were significantly greater in hypertension patients with LVRM compared with those without LVRM. Multivariate regression analysis demonstrated that body mass index and galectin‐3 were independent predictors of LVRM in the hypertension group. Only left ventricular mass was independently correlated with serum galectin‐3 levels in patients with hypertension. The receiver operating characteristic analysis showed an area under the curve for galectin‐3 of 0.698 ( P <.001), with an optimal cutoff of 9.43 ng/mL. Therefore, galectin‐3 is independently correlated with LVRM and can be regarded as a valuable biomarker of early cardiac remodeling of hypertension.